Marinobacter subterrani, a genetically tractable neutrophilic Fe(II)-oxidizing strain isolated from the Soudan Iron Mine - Bonis, Benjamin M.; Gralnick, Jeffrey A. (Frontiers in Microbiology, 2015)
We report the isolation, characterization, and development of a robust genetic system for a halophilic, Fe(II)-oxidizing bacterium isolated from a vertical borehole originating 714 m below the surface located in the Soudan Iron Mine in northern Minnesota, USA. Sequence analysis of the 16S rRNA gene places the isolate in the genus Marinobacter of the Gammaproteobacteria. The genome of the isolate was sequenced using a combination of short- and long-read technologies resulting in 2 contigs representing a 4.4 Mbp genome. Using genomic information, we used a suicide vector for targeted deletion of specific flagellin genes, resulting in a motility-deficient mutant. The motility mutant was successfully complemented by expression of the deleted genes in trans. Random mutagenesis using a transposon was also achieved. Capable of heterotrophic growth, this isolate represents a microaerophilic Fe(II)-oxidizing species for which a system for both directed and random mutagenesis has been established. Analysis of 16S rDNA suggests Marinobacter represents a major taxon in the mine, and genetic interrogation of this genus may offer insight into the structure of deep subsurface communities as well as an additional tool for analyzing nutrient and element cycling in the subsurface ecosystem.